Life quality impairment caused by hookworm-related cutaneous larva migrans in resource-poor communities in Manaus, Brazil. - Angela Schuster; Hannah Lesshafft; Sinésio Talhari; Silás Guedes de Oliveira; Ralf Ignatius; Hermann Feldmeier (Public Library of Science (PLoS), 2011)
BACKGROUND: Hookworm-related cutaneous larva migrans (CLM) is a common but neglected tropical skin disease caused by the migration of animal hookworm larvae in the epidermis. The disease causes intense pruritus and is associated with important morbidity. The extent to which CLM impairs skin disease-associated life quality has never been studied. METHODS: A modified version of the Dermatology Life Quality Index (mDLQI) was used to determine skin disease-associated life quality in 91 adult and child patients with CLM, living in resource-poor communities in Manaus, Brazil. Symptoms and signs were documented and skin disease-associated life quality was semi-quantitatively assessed using mDLQI scores. The assessment was repeated two and four weeks after treatment with ivermectin. RESULTS: Ninety-one point five percent of the study participants showed a considerable reduction of skin disease-associated life quality at the time of diagnosis. The degree of impairment correlated with the intensity of infection (rho = 0.76, p<0.001), the number of body areas affected (rho = 0.30; p = 0.004), and the presence of lesions on visible areas of the skin (p = 0.002). Intense pruritus, sleep disturbance (due to itching) and the feeling of shame were the most frequent skin disease-associated life quality restrictions (reported by 93.4%, 73.6%, and 64.8% of the patients, respectively). No differences were observed in skin disease-associated life quality restriction between boys and girls or men and women. Two weeks after treatment with ivermectin, skin disease-associated life quality improved significantly. After four weeks, 73.3% of the patients considered their disease-associated life quality to have returned to normal. CONCLUSIONS: CLM significantly impaired the skin disease-associated life quality in child and adult patients living in urban slums in North Brazil. After treatment with ivermectin, life quality normalised rapidly.